Risk factors for fecal incontinence after surgery for cryptoglandular anal fistula: Protocol of a meta-analytic study - Cheng Tang; Zubing Mei (PLoS ONE, 2026)
Introduction Fecal incontinence after anal fistula surgery is a feared functional complication that can impair dignity, social participation, and quality of life. Reported rates vary widely across procedures and fistula phenotypes, and individual studies suggest multiple patient-, disease-, and surgery-related predictors. However, the prognostic evidence remains dispersed, with inconsistent outcome definitions and variable adjustment for confounding. This protocol describes a systematic review and quantitative synthesis to identify factors associated with postoperative fecal incontinence after surgery for cryptoglandular anal fistula. Methods and analysis The study will follow the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols guidance. PubMed, Embase, Cochrane Library, Web of Science, and grey-literature sources will be searched from inception to January 11, 2026, without language restrictions. Eligible studies will be cohort or case-control studies of adults undergoing surgery for cryptoglandular anal fistula that report new-onset or worsening postoperative fecal incontinence using validated scores or clearly defined clinical criteria at least 3 months after surgery. Two reviewers will independently screen records, extract data, and assess risk of bias using the Quality in Prognosis Studies tool and, where applicable, the Newcastle-Ottawa Scale. Adjusted estimates will be prioritized for random-effects meta-analysis when studies are clinically comparable. Heterogeneity and confounding will be explored by fistula complexity, procedure type, follow-up duration, and baseline continence assessment. Certainty of evidence will be rated using a prognostic-factor approach. Discussion By integrating observational evidence across diverse surgical strategies, this review aims to generate pooled, evidence-based prognostic estimates for postoperative fecal incontinence. The findings may support preoperative counseling, baseline continence assessment, individualized procedure selection, sphincter imaging where appropriate, and targeted strategies to reduce preventable functional harm. Ethics and Dissemination No ethical approval is required as this study uses existing data. Results will be disseminated through peer-reviewed journals and conferences to inform anal fistula management. Registration International Prospective Register of Systematic Reviews (CRD420261283433)